5,5′′-Dibromo-1,1′′-bis(prop-2-en-1-yl)-1,1′′,2,2′′-tetrahydrodispiro[indole-3,7′-[6,9]diazatricyclo[7.3.0.0(2,6)]dodecane-8′,3′′-indole]-2,2′′-dione - Al Mamari, Khalil (International Union of Crystallography, 2012)
In the molecule of the title compound, C(30)H(30)Br(2)N(4)O(2), the piperazine ring adopts a chair conformation. The pyrrolidine rings that are fused to the piperazine ring adopt envelope conformations (in which the N atom represents the flap). The indoline fused-ring systems are nearly planar (r.m.s. deviations = 0.009 and 0.019 Å); the two fused rings are aligned at 60.63 (6)°.